Penerapan Pembelajaran Berbasis Literasi Ekologi untuk Meningkatkan Kemampuan Berpikir Kritis Siswa di SMA Negeri 2 Peusangan - Sri Novayanti; Muslihin Muslihin (Universitas Garut, 2026)
This study aimed to determine the implementation of ecological literacy-based learning in improving students' critical thinking skills at State Senior High School 2 Peusangan. The research employed a quantitative approach using a pre-experimental design with a One-Group Pretest–Posttest Design. The sample consisted of 30 tenth-grade students selected through purposive sampling. Data were collected using a critical thinking skills test consisting of 20 multiple-choice questions administered during the pretest and posttest. The data were analyzed using the normality test, homogeneity test, and paired sample t-test. Furthermore, the effectiveness of the improvement in students' critical thinking skills was evaluated using the Normalized Gain (N-Gain). The results showed that the implementation of ecological literacy-based learning significantly improved students' critical thinking skills at State Senior High School 2 Peusangan. This finding was supported by the paired sample t-test results, which indicated that the calculated t-value (8.77) was greater than the critical t-value (1.67), leading to the rejection of the null hypothesis (H₀) and the acceptance of the alternative hypothesis (H₁). All aspects of critical thinking in ecology learning showed improvement, including reasoning with an N-Gain of 79.24% (high), analysis with 77.95% (high), inference with 74.07% (high), evaluation with 70.34% (high), and reflection with 60.12% (moderate). Therefore, the implementation of ecological literacy-based learning can serve as an alternative instructional approach to improve students' critical thinking skills in ecology learning.Keywords: Ecological literacy-based learning, critical thinking skills, State Senior High School 2 Peusangan